Food for all in Africa sustainable intensification for African farmers - Conway, Gordon 1938-2023; Badiane, Ousmane; Glatzel, Katrin (Comstock Publishing Associates, an imprint of Cornell University Press, 2019)
African farms and farmers -- Hunger and malnutrition -- The threats to food security -- Resilient farmers -- Sustainable agriculture -- Agriculture and ecology -- The new genetics -- Value chains -- Digital farmers -- Transforming agriculture -- Leadership and performance
Includes bibliographical references and index
Keywords: Ernährungssicherung / (DE-627)091379369 / (DE-STW)13428-4; Landwirtschaft / (DE-627)091374189 / (DE-STW)12945-3; Nachhaltigkeit / (DE-627)570372119 / (DE-STW)29102-5; Faktorintensität / (DE-627)091359171 / (DE-STW)10313-1; Kleinbauern / (DE-627)091374286 / (DE-STW)18093-5; Produktivität / (DE-627)091384575 / (DE-STW)10460-2; Landwirtschaftliche Entwicklung / (DE-627)091374235 / (DE-STW)10505-6; Subsahara-Afrika / (DE-627)091345804 / (DE-STW)17652-0; Afrika / (DE-627)091345790 / (DE-STW)17642-3; Food security / Africa, Sub-Saharan; Agricultural intensification / Africa, Sub-Saharan; Sustainable agriculture / Africa, Sub-Saharan; Produce trade / Africa, Sub-Saharan; Farms, Small / Africa, Sub-Saharan